Subacromial balloon spacer for irreparable rotator cuff tears of the shoulder (START:REACTS): a group-sequential, double-blind, multicentre randomised controlled trial. Issue 10339 (21st May 2022) - Metcalfe, Andrew; Parsons, Helen; Parsons, Nicholas; Brown, Jaclyn; Fox, Josephine; Gemperlé Mannion, Elke; Haque, Aminul; Hutchinson, Charles; Kearney, Rebecca; Khan, Iftekhar; Lawrence, Tom; Mason, James; et al.
Summary: Background: New surgical procedures can expose patients to harm and should be carefully evaluated before widespread use. The InSpace balloon (Stryker, USA) is an innovative surgical device used to treat people with rotator cuff tears that cannot be repaired. We aimed to determine the effectiveness of the InSpace balloon for people with irreparable rotator cuff tears. Methods: We conducted a double-blind, group-sequential, adaptive randomised controlled trial in 24 hospitals in the UK, comparing arthroscopic debridement of the subacromial space with biceps tenotomy (debridement only group) with the same procedure but including insertion of the InSpace balloon (debridement with device group). Participants had an irreparable rotator cuff tear, which had not resolved with conservative treatment, and they had symptoms warranting surgery. Eligibility was confirmed intraoperatively before randomly assigning (1:1) participants to a treatment group using a remote computer system. Participants and assessors were masked to group assignment. Masking was achieved by using identical incisions for both procedures, blinding the operation note, and a consistent rehabilitation programme was offered regardless of group allocation. The primary outcome was the Oxford Shoulder Score at 12 months. Pre-trial simulations using data from early and late timepoints informed stopping boundaries for two interim analyses. The primary analysis was on a modified intention-to-treat basis, adjusted for the planned interim analysis. The trial was registered with ISRCTN, ISRCTN17825590. Findings: Between June 1, 2018, and July 30, 2020, we assessed 385 people for eligibility, of which 317 were eligible. 249 (79%) people consented for inclusion in the study. 117 participants were randomly allocated to a treatment group, 61 participants to the debridement only group and 56 to the debridement with device group. A predefined stopping boundary was met at the first interim analysis and recruitment stopped with 117 participants randomised. 43% of participants were female, 57% were male. We obtained primary outcome data for 114 (97%) participants. The mean Oxford Shoulder Score at 12 months was 34·3 (SD 11·1) in the debridement only group and 30·3 (10·9) in the debridement with device group (mean difference adjusted for adaptive design –4·2 [95% CI –8·2 to –0·26];p=0·037) favouring control. There was no difference in adverse events between the two groups. Interpretation: In an efficient, adaptive trial design, our results favoured the debridement only group. We do not recommend the InSpace balloon for the treatment of irreparable rotator cuff tears. Funding: Efficacy and Mechanism Evaluation Programme, a Medical Research Council and National Institute for Health and Care Research partnership